2014
DOI: 10.1159/000361056
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Electroretinograms in Stargardt's Disease/Fundus Flavimaculatus

Abstract: Purpose: To determine whether the characteristics of multifocal electroretinograms (mfERGs) were correlated with the ophthalmic appearance of the fundus in patients with Stargardt's disease/fundus flavimaculatus (SFF). Methods: Full-field ERGs, mfERGs, and general ophthalmic examinations were performed on 49 eyes with SFF. Results: The SFF patients were divided into four subtypes according to the classification of Noble and Carr [Arch Ophthalmol 1979;97:1281-1285]. The patients with type 1 SFF had severely red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The cone responses (photopic b-wave) were significantly reduced in SFF, and the retinal function was the worst in SFF type 3E [4]. The full-field and multifocal ERG findings in our patients [2] are in good agreement with the results presented in the paper by Itabashi et al [4]. …”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…The cone responses (photopic b-wave) were significantly reduced in SFF, and the retinal function was the worst in SFF type 3E [4]. The full-field and multifocal ERG findings in our patients [2] are in good agreement with the results presented in the paper by Itabashi et al [4]. …”
Section: Figsupporting
confidence: 90%
“…1e). As shown previously [table 1 in [2]], the BCVA and the multifocal ERGs' responses appear to depend more on the fundus appearance including SFF type than on age. However, Itabashi et al [4] reported, for each patient, that the BCVA in eyes with SFF decreased with increasing age, and 25% of the patients over 40 years became legally blind.…”
Section: Figsupporting
confidence: 68%
See 1 more Smart Citation
“…Electroretinographic tests, such as multifocal electroretinography (mfERG) [17,18] (Figure 7), pattern ERG (PERG) [19] ( Figure 8) and flash full-field ERG (ERG) [10,11], are helpful in confirming the diagnosis and have prognostic value in STGD. These tests estimate objectively actually generalized bioelectrical function of the retina including the macular region.…”
Section: Electroretinographymentioning
confidence: 99%
“…We congratulate Kuniyoshi et al [1] on their study entitled ‘Multifocal electroretinograms in Stargardt's disease/fundus flavimaculatus'. The authors grouped their patients into 4 types according to the classification by Noble and Carr [2].…”
mentioning
confidence: 99%